Allometric equations to estimate the above-ground biomass of trees in the tropical secondary forests of different ages - Karyati Karyati; ISA B. IPOR; ISMAIL JUSOH; MOHD. EFFENDI WASLI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Karyati, Ipor IB, Jusoh I, Wasli ME. 2019. Allometric equations to estimate the above-ground biomass of trees in the tropical secondary forests of different ages. Biodiversitas 20: 2427-2436. The allometric equations for trees of secondary forests of different ages in abandoned lands after shifting cultivation are still rarely available. The objective of this study was to develop allometric equations to estimate the above-ground biomass (AGB) of trees (DBH of > 5 cm) in the tropical secondary forest of different ages, namely 5, 10, and 20 years after abandonment. The selected trees in this study represented the dominant and rare species and DBH classes in each study site. The trunk dry biomass and AGB showed strong correlations (adjusted R2= 0.59-0.95) with diameter at breast height (DBH) and height. The leaf and branch dry biomass had weak correlations with height (adjusted R2=0.36-0.50). The developed allometric equations were suitable for trees of secondary forests of different ages, because the selected samples used in the destructive method were based on a field inventory data of forest structure and floristic composition.